PENGEMBANGAN MODEL PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN KECAKAPAN HIDUP : Studi pada Mata Pelajaran Ilmu Pengetahuan Sosial Program Paket B di Kabupaten Karanganyar Provinsi Jawa Tengah - HALIMAH, Nur (2009)
The dissertation is entitled "Developing the Contextual Teaching and Learning (CTL) Model to Improve the Life Skills", conducted in Sosial Studie subject, Exuivalency Program Package B of non-formal education. Life skill education should be delivered to the learners of all kinds of non-formal education. However, because of much restrictedness, not every program is able to deliver life skill education. WHO (in ICAP.org. 2007: 1) defines life skill as abilities for adaptive and positive behavior that enable individuals to deal effectively with the demands and challenges of everyday life. According to Sumantri (2004: 23) the aim of life skill is to develop attitude, willingness, self management, academic, socia,l and vocational skill. Susilana (2006 : 75) says that education oriented to life skills is part of the integrated curriculum, because the development of life skill should be integrated to the other subjects. Drake (2004: 6) state that the integrated curriculum is a matter of making interrelationship among the subjects, relation with the life, and interconnection between skill and knowledge. In delivering the life skill education, Ali (2007: 1281) emphasizes the importance of an interdisciplinary approach and paying attention on the contextual need of the learners. In Social studies, Gross (Muchtar, 2007: 31) suggest the Social Studies should be related to the environment and community where the school locates. Sumantri (2004: 25) stated that CTL is a model that leads to development of life skill. In the context of social studies learning, Nursi (2007:7) contends that it has to be directed toward the building of soft skills and the learning model that is able to develop the soft skills is the one that orients to the learners such as CTL. This study adopts the method of Research and Development resulting in CTL model to improve the life skill in social studies of Package B Program. Such model shows its high effectiveness internally and externally. Internally, the effectiveness is analyzed through t-test that indicates a significant difference between pre-test and post-test scores. Externally, the effectiveness of the CTL model is analyzed through Anova test that shows the fact score of life skill of the experiment group is higher than that of control group. Beside that, the CTL model also shows high internal effectiveness in increasing the learning achievement of Social studies, indicated by significant difference between pre-test and post-test score. Externally, however, not all of the experiment group shows better result in improving achievement of social studies learning. Based on the study, it is recommended to the Directorate of Equality Education, Directorate of PTK-PNF, Education Office, and tutors make use of the research findings as a reference to which policies are made for the provision of life skill education at large. The future researcher are recommended to expand the scope and focus of research into other fields and aspects.